Absolute bioavailability and safety of a novel rivastigmine nasal spray in healthy elderly individuals. (26th October 2016) - Morgan, Timothy M.; Soh, Bob
Abstract : Aims: To test the feasibility of a novel rivastigmine nasal spray as prospective treatment for dementia. Methods: A single dose, crossover absolute bioavailability and safety study was conducted with rivastigmine intravenous solution (1 mg) and nasal spray (3.126 mg) in eight healthy elderly individuals, aged 58–75 years. Results: Absolute bioavailability ( F ) of the nasal spray was significant at 0.62 (0.15) for F  > 0 ( P  < 0.001, n  = 8). The systemic dose absorbed was 2.0 (0.6) mg, time to maximum plasma concentration was 1.1 (0.5) h and maximum plasma concentration was 6.9 (2.0) ng ml −1 . The NAP226–90 to rivastigmine AUC0–∞ ratio was 0.78 (0.19). The single dose safety was good with two of five mild adverse events related to the nasal spray. Nasal and throat irritation were perceived as mild and transient, and both had resolved at 20 min post‐nasal dose. An estimated dose of two or three sprays twice‐daily with nasal spray would deliver comparable rivastigmine exposure and efficacy as a 6–9.7 mg day –1 oral dose and a 10 cm 2 transdermal patch, respectively. Conclusions: The rivastigmine nasal spray had superior absolute bioavailability compared to historical values for oral capsule and transdermal patch determined by other researchers. It had rapid onset of action, low NAP226–90 to rivastigmine exposure ratio and a favourable safety and tolerability profile. The ability to achieve adjustable, individual, twice‐daily dosing during waking hours has good potential to minimise undesirable cholinergic burden and sleep disturbances whilst delivering an effective dose for the treatment of dementia associated with Alzheimer's and Parkinson's disease.